2016
DOI: 10.1186/s12985-016-0644-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of hydropericardium syndrome outbreak-associated serotype 4 fowl adenovirus isolates in central China

Abstract: In several parts of China, there have been a large number of hydropericardium syndrome (HPS) outbreaks caused by serotype 4 fowl adenovirus (FAdV­4) in broiler chickens since 2015. These outbreak-associated FAdV-4 strains were distinct from previous circulating strains which did not lead to severe HPS outbreaks. To better understand the molecular epidemiology of the currently circulating FAdV strains for effective diagnosis and treatment of HPS, we isolated 12 HPS outbreak-associated FAdV-4 strains from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…In a similar way to the majority of more recent FAdV screenings studies (Changjing et al., ; De la Torre et al., ; Zhang et al., ), we have applied molecular typing based on the hexon loop‐1 for classification of the detected FAdV strains, replacing the traditional methods of serological cross‐neutralization assays and restriction fragment length polymorphism (Hess, ). Although these tests have served as the basis for typing of isolates, these methods of characterization are costly, require reference sera and are sometimes unable to differentiate between serotypes (Changjing et al., ; Hess, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way to the majority of more recent FAdV screenings studies (Changjing et al., ; De la Torre et al., ; Zhang et al., ), we have applied molecular typing based on the hexon loop‐1 for classification of the detected FAdV strains, replacing the traditional methods of serological cross‐neutralization assays and restriction fragment length polymorphism (Hess, ). Although these tests have served as the basis for typing of isolates, these methods of characterization are costly, require reference sera and are sometimes unable to differentiate between serotypes (Changjing et al., ; Hess, ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, outbreaks of FAdVs have been frequently reported worldwide. Over the past 5 years, epidemics with mixed serotypes have been observed in different regions, such as FAdV-2, -11, -7 and -8 in Europe and North America, 7 , 35 , 36 , 37 FAdV-4 in Asia 5 , 38 , 39 , 40 , 41 and FAdV-2 and -8b in South Africa. 42 , 43 The most notable diseases associated with FAdV infection in chickens are IBH, HHS and GE.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 Phylogenetic analysis of the hexon gene has revealed that strains circulating in China before 2014 and after 2015 had different ancestors, and that new strains circulating in China were derived from earlier Indian strains. 39 The genome sequences of the contemporary strains have also been analyzed and clustered. This new pandemic FAdV-4 strain virus can be characterized by the notable nucleotide deletions in ORFs 19 and 27.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2015, severe outbreaks of HHS have occurred in commercial duck farms in Jiangsu, Anhui, Hubei, Jiangxi, Shandong, and Henan Provinces, China, resulting in high mortalities, pericardial effusion, and stunted growth among ducks (Chen et al, 2016 ; Yu et al, 2018 ). Several previous studies have focused on the epidemiology (Liu et al, 2015 ; Zhang et al, 2016 ; Li et al, 2017 ), gene structure (Mase et al, 2009 ; Griffin and Nagy, 2011 ; Shah et al, 2016 ), diagnostic detection (Günes et al, 2012 ; Junnu et al, 2014 ; Niczyporuk et al, 2015 ; Wang et al, 2017 ), and vaccine strategies (Schonewille et al, 2010 ; Shah et al, 2012 , 2017 ) for the disease. Unfortunately, little is known about the pathogenicity of this virus in Cherry Valley meat ducks, except that intracerebral infection caused a 15% mortality rate (Chen et al, 2016 ) and oral infection showed no clinical signs (Pan et al, 2017 ); therefore, to complete the pathogenicity of the virus, Cherry Valley meat ducks were infected with FAdV-4 in this study.…”
Section: Introductionmentioning
confidence: 99%